The Effect of Lamtoro Leaf POC and Tofu Liquid Waste on the Growth of Cayenne Chili (Capsicum frutescens) - Siska Andriyani; Suparti Suparti (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Liquid organic fertilizer is a fermented solution of organic plant residues, animal and human feces containing nutrients. Lamtoro and tofu liquid waste contain N, P, K, Mg, and Ca, which are suspected to have the potential for liquid organic fertilizer to increase the growth of cayenne pepper (C. frutescens). This study aims to determine the effect of giving POC from lamtoro leaves and tofu liquid waste on the growth of cayenne pepper (C. frutescens). Methods: This study used a completely randomized design (CRD) with two replications. POC volume 1:1 consisted of two-liter lamtoro leaf extract and 2-liter tofu liquid waste. The first factor is the volume concentration of POC with the respective concentrations of V0: 0%, V1: 10%, V2: 20%, and V3: 30%. The second factor is the time of spraying POC T1: 3 days interval and T2: 6 days interval. Parameters measured included plant height (cm), number of leaves (strands), and plant fresh weight (g). Results: 20% volume (V2) with three-day intervals (T1) gave the best results for plant height (20.10 cm), number of leaves (7.00 leaves), and plant fresh weight (11.50 g). 0% volume (V0) with an interval of 6 days (T2) gave the lowest yield on plant height (6.35 cm), number of leaves (3.00 leaves), and fresh weight of plants (3.00 leaves). Conclusions: Application POC from lamtoro leaves and tofu liquid waste can potentially increase the growth of cayenne pepper (C. frutescens).